Experience in ensuring the competitiveness of coastal regions in the European Union and all over the world - Bezkhlibna, Anastasiia; Gudz, Petro; Puhalska, Gulnara (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The article discusses the experience of ensuring the competitiveness of coastal regions in the EU and in the world. It has been established that socio-economic processes in coastal regions play a key role in ensuring their competitiveness on a global scale. The research is based on the description of experience according to the structural elements of competitiveness - “territory”, “people”, “business processes”, “administration”. EU initiatives address key priorities for enhancing regional capacity for innovation, competitiveness, sustainable jobs, conditions that create growth for institutional, financial and regulatory support for regions, and Smart specialization strategies for regions aimed at increasing added value, building on regional competitive advantages and developing interregional cooperation. Considering the world experience of management of the maritime sector, it is necessary to note the effectiveness of the use of incentives. Among them there can be found economic (fisheries and aquaculture, biotechnology and marine shelf research), recreational, energy and shipbuilding, logistics, educational, ecosystem and environmental activities. It should be noted that the existence of a clear EU blue growth strategy, marine development strategies (subordinate to the EU regional development strategy) allow local and regional authorities to use existing tools to create highly skilled jobs and economic opportunities in the maritime sector (taking into account the specifics of each region). Noteworthy are the strategies of smart-specialization and high-tech sectors that require some education, skills and experience of specialists (biotechnology, research of the sea shelf with the help of robotics, etc.) 2. The functioning of maritime clusters is an example of an effective way to integrate maritime and related industries, promote international trade, increase the region's added value, increase employment in the region, improve staff skills, develop and improve technology. 3. The growth of value added in the maritime sector depends on the level of development of regional infrastructure and related sectors. A clear example of the creation of a regional ecosystem in the region is the Oslo Maritime Region, which, through the use of three principles - infrastructure, digitalization and science - has become one of the EU’s leading regions in terms of added value in the economy.